Development of Flip PDF Corporate Edition Based Learning Media on Price Index Material at SMA Negeri 3 Banjarbaru - Putri, Sheila Haifa; Rahmattullah, Muhammad; Ratumbuysang, Monry Fraick Nicky Gillian; Hasanah, Mahmudah (Jurnal Manajemen, 2023)
Learning media is one of the important supports that can be used in learning activities. In this study the was to develop flip PDF corporate edition-based learning media on price index material. The discussion is carried out measure the feasibility of learning media and influence of learning media on learning outcomes perice index material. This research is included in research and development with the ADDIE development model. Media feasibility assessment is validated by media experts, material experts, and practitioners. Measurement of learning outcomes using the Pretest-Posttest Control Group Design. Learning media result validated by media experts obtained an average score of 4.43 very good criteria and an assessment of the percentage of 88.61% in the very decent category. The results material expert validation obtained an average rating of 4.29 very good criteria and a percentage of 85.84% very feasible category. In limited field trials the average rating was 4.35 very good criteria and 86.88% very feasible category. While the operational field trials obtained an average score of 4.33 very good criteria and a percentage of 86.43% very feasible category. Overall obtaining an average score of 4.35 very good criteria and a percentage of 86.94% very feasible category. Testing the influence of the media learning outcomes using the Wilcoxon test, the results of the experimental and control groups obtained the same significance value, namely <0.001 < 0.05. Meanwhile, the Mann Whitney test yielded a significance value of 0.032 < 0.05.